Documentary evidence: Navigating identity and credibility in Africa's urban estuaries. - Rasmussen, Jacob; Wafer, Alex (African Studies, 2019)
In this article we argue for closer intellectual attention to the intersection between the unstable materiality of urban spaces on the one hand, and anxieties about the materiality of official documents on the other. Based on initial evidence from two cities in Africa, namely Nairobi and Johannesburg, we have observed that official documents as material objects matters most in precisely those parts of the city where formal state and civil society institutions appears most absent, i.e. those marginal or estuarial urban spaces, characterised by precarity, informality and mobility, where the majority of African urban residents reside. This is because anxieties about credibility, legitimacy and belonging are most acute in precisely these grey spaces. Yet we argue that the preoccupation with the materiality of these documents does not only reflect broader anxieties about inclusion into or exclusion from the wider urban economy. Instead we suggest that the materiality of documents is more deeply implicated into the unstable material conditions which characterise these estuarial spaces. As these estuarial spaces manifest fluid and sometimes illegible forms of policing and social order, so the variable material qualities of documents simultaneously proffers or eschews the credibility of the bearer in particular situations. This ambiguous relationship to absolute status subverts the bio-political pretensions of contemporary institutions of government, but serves as a crucial tactical vocabulary in navigating the precarious and unstable materiality of the contemporary African city. While the evidence presented here is drawn from ethnographic research in two such 'urban estuaries', we suggest that these observations might resonate more broadly, and might open up new avenues for thinking about the relationship between the material and the bio-political in Africa.